PENGEMBANGAN HUTAN SEKIPAN SEBAGAI WANA WISATA DI TAWANGMANGU DENGAN PENERAPAN PRINSIP EKOWISATA DAN ARSITEKTUR HIJAU - Ichsan Mustofa; Hadi Setyawan; Hari Yuliarso (ARSITEKTURA, 2014)
Abstract: Forest Sekipan Tawangmangu have very interesting potential with special features pine forests, forest quinine, orchids and wildlife such as birds at Forest Sekipan. But all that is not enough to attract visitors because of the division and circulation zone that has not been regular and the limited facilities available in the Forest Sekipan. Conditions of flora and fauna are also threatened because taken and hunted. Therefore Forest Sekipan have developed to become an attractive tourist spot. In addition, the expansion also aims to preserve biodiversity contained in the forest. The question is how to develop a design that was once Forest Sekipan campground become wana trips to tourist activities, education, research or conservation. The method used is the application of the principles of Ecotourism and Green Architecture. The result was the design of a tourist wana Sekipan more landscaped and attractive tourist activities, education, research or conservation. Keywords: Forest Tourist, Ecotourism, Green Architecture